Metal carbide coated material and method for manufacturing metal carbide coated material
Patent Information
- Application Number
- JP2025059765
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0009】 本発明によれば、耐久性がさらに向上した炭化金属被覆膜材料及びその炭化金属被覆膜材料の製造方法を提供することができる。
Smart Images

Figure 2026166672000002 
Figure 2026166672000003 
Figure 2026166672000004
Abstract
Description
[Technical Field]
[0001] The present invention relates to a metal carbide coated material comprising a carbon substrate mainly composed of carbon and a metal carbide coated film mainly composed of metal carbide that coats at least a portion of the carbon substrate, and to a method for producing the metal carbide coated film material. [Background technology]
[0002] Carbides such as tantalum carbide, niobium carbide, zirconium carbide, hafnium carbide, and tungsten carbide have high melting points and excellent chemical stability, strength, toughness, and corrosion resistance. Therefore, coating a carbon substrate with a carbide can improve the properties of the carbon substrate, such as heat resistance, chemical stability, strength, toughness, and corrosion resistance. Carbide-coated materials, particularly tantalum carbide-coated carbon materials, which have a carbide film coated on the surface of a carbon substrate, are used as components in semiconductor single crystal manufacturing equipment for materials such as Si (silicon), SiC (silicon carbide), GaN (gallium nitride), and AlN (aluminum nitride).
[0003] Sublimation recrystallization is a widely known method for producing bulk single crystals of SiC. In sublimation recrystallization, SiC raw material is packed into a crucible, and a SiC seed crystal is placed on top of it. Guide materials are also placed around the SiC seed crystal to direct the sublimation gas towards the single crystal. The sublimation gas generated by heating the SiC raw material rises along the inner wall of the guide material, and a SiC single crystal grows on the SiC seed crystal.
[0004] Furthermore, SiC single-crystal substrates used in semiconductor devices and other applications are manufactured by epitaxially growing SiC single crystals on SiC substrates made of bulk single crystals. Methods for epitaxial growth of SiC single crystals include liquid-phase epitaxy (LPE), vapor-phase epitaxy (VPE), and chemical vapor deposition (CVD). Typically, the CVD method is used for epitaxial growth of SiC single crystals. In the CVD method, a SiC substrate is placed on a susceptor within the apparatus, and a raw material gas is supplied under high-temperature conditions of 1500°C or higher to grow the SiC single crystal.
[0005] In a method for manufacturing such SiC single crystals, Patent Document 1 discloses a method using a crucible in which the inner surface of a graphite substrate is coated with tantalum carbide in order to obtain higher quality crystals. Patent Document 2 also discloses a method using a guide member in which the inner wall is coated with tantalum carbide. [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] Japanese Patent Publication No. 2019-99453 [Patent Document 2] Japanese Patent Publication No. 2019-108611 [Overview of the project] [Problems that the invention aims to solve]
[0007] It is known that compound semiconductor single crystals grown using metal carbide-coated materials as crucibles, guide members, and susceptors exhibit a significantly improved crystal growth yield compared to cases where uncoated carbon materials are used. On the other hand, compound semiconductor crystal growth is still in the developing stage, and cost reduction in the manufacturing process is important. In general, metal carbide coatings such as tantalum carbide, niobium carbide, zirconium carbide, hafnium carbide, and tungsten carbide are expensive, so if device members such as crucibles, guide members, and susceptors using these can be used repeatedly, the cost of single crystals will be significantly reduced. In order to further increase the number of repeated uses of the device members, it is desirable to further improve the durability of the device members. Accordingly, an object of the present invention is to provide a metal carbide coating film material with further improved durability and a method for producing the metal carbide coating film material. [Means for Solving the Problems]
[0008] As a result of intensive studies, the present inventors have found that the durability of the metal carbide coating material can be further improved by allowing pinholes to exist at a density of 10 to 10000 per mm on at least a part of the surface of the metal carbide coating material, and have completed the present invention. The gist of the present invention is as follows. 2 The present inventors have found that the durability of the metal carbide coating material can be further improved by allowing pinholes to exist at a density of 10 to 10000 per mm on at least a part of the surface of the metal carbide coating material, and have completed the present invention. The gist of the present invention is as follows. [1] A metal carbide coating material comprising a carbon base material containing carbon as a main component, and a metal carbide coating film containing a metal carbide as a main component that covers at least a part of the carbon base material, A metal carbide coating material in which pinholes are present at a density of 10 to 10000 per mm on at least a part of the surface of the metal carbide coating material. 2 A metal carbide coating material in which pinholes are present at a density of 10 to 10000 per mm on at least a part of the surface of the metal carbide coating material. [2] The metal carbide coating material according to the above [1], wherein the average value of the minor diameters of the pinholes is 0.1 to 4.0 μm. [3] The metal carbide coating material according to the above [1] or [2], wherein the metal carbide coating film contains, as a main component, at least one metal carbide selected from the group consisting of tantalum carbide, niobium carbide, zirconium carbide, hafnium carbide, and tungsten carbide. [4] The carbon base material has a thermal expansion coefficient of 4.0 to 8.0×10 -6 / °C, the metal carbide coating material according to any one of the above [1] to [3]. [5] The metal carbide coating material according to any one of [1] to [4] above, wherein the thickness of the metal carbide coating film is 3 to 100 μm. [6] A method for producing a metal carbide coated material according to any one of [1] to [5] above, comprising the step of forming the metal carbide coating film on the surface of the carbon substrate by a CVD reaction using a metal chloride gas and a hydrocarbon gas. [7] A method for producing a metal carbide coated material according to [6] above, wherein the metal carbide coated film is formed in a temperature environment of 800 to 2200°C. [8] A method for producing a metal carbide coated material according to [6] or [7], further comprising the step of annealing the carbon substrate having the metal carbide coating film formed on its surface at a high temperature of 800 to 2200°C and a reduced pressure of 1 to 1000 Pa. [Effects of the Invention]
[0009] According to the present invention, it is possible to provide a metal carbide coating material with further improved durability and a method for manufacturing the metal carbide coating material. [Brief explanation of the drawing]
[0010] [Figure 1] Figure 1 is a schematic diagram of an example of an externally heated, reduced-pressure CVD apparatus used to form a tantalum carbide coating film on the surface of a carbon substrate. [Figure 2] Figure 2 is a schematic diagram of an example of a vacuum heating furnace for semiconductor single crystal growth. [Figure 3] Figure 3 is a graph showing the relationship between pinhole density and the number of repeated uses in Examples 1 to 17 and Comparative Example 1. [Modes for carrying out the invention]
[0011] [Metal carbide coating material] The metal carbide coating material of the present invention comprises a carbon substrate mainly composed of carbon and a metal carbide coating film mainly composed of metal carbide that coats at least a portion of the carbon substrate. Furthermore, at least a portion of the surface of the metal carbide coating material of the present invention contains 10 to 10,000 particles / mm². 2Pinholes exist at a certain density. This can further improve the durability of the metal carbide coating material.
[0012] Examples of metal carbide coatings include coatings of high-melting-point metal carbides such as tantalum carbide, niobium carbide, zirconium carbide, hafnium carbide, and tungsten carbide, as well as composite metal carbide coatings made by combining two or more of these metal carbides. Among these metal carbide coatings, tantalum carbide coatings are preferred. The present invention's metal carbide coating material will be explained below, using a tantalum carbide coating material, which uses tantalum carbide as the carbide and carbon as the base material, as an example.
[0013] [Regarding tantalum carbide coating materials] A tantalum carbide coating material according to one embodiment of the present invention will be described below with reference to Figure 1. A tantalum carbide coated material according to one embodiment of the present invention comprises a substrate mainly composed of carbon and a tantalum carbide coated film mainly composed of tantalum carbide provided on the surface of the substrate. The tantalum carbide coated film may cover a part of the carbon substrate or the entire carbon substrate.
[0014] As the carbon substrate 14, for example, a carbon material substrate such as isotropic graphite, extruded graphite, pyrolytic graphite, or carbon fiber reinforced carbon composite material (C / C composite) can be used. The carbon substrate 14 is not particularly limited as long as it includes a cylindrical portion with a cylindrical shape. The carbon substrate 14 can be processed into a shape appropriate for the application.
[0015] A tantalum carbide coated material according to one embodiment of the present invention can be manufactured by forming a tantalum carbide coating film on the surface of a carbon substrate. The tantalum carbide coating film can be formed on the surface of the carbon substrate 14 by methods such as chemical vapor deposition (CVD), sintering, or carbonization. Among these, the CVD method is preferred as a method for forming the tantalum carbide coating film because it can form a uniform and dense film.
[0016] Furthermore, CVD methods include, for example, thermal CVD, photoCVD, and plasma CVD, and thermal CVD can be used to form tantalum carbide coatings. Thermal CVD has advantages such as a relatively simple apparatus configuration and no damage caused by plasma. Formation of tantalum carbide coatings by thermal CVD can be carried out, for example, using an externally heated vacuum CVD apparatus 10 as shown in Figure 1. In the externally heated vacuum CVD apparatus 10, the carbon substrate 14 is supported by support means 15 in a reaction chamber 12 equipped with a heater 13, a raw material supply unit 16, an exhaust unit 17, etc.
[0017] A method for producing a tantalum carbide coated material according to one embodiment of the present invention will be described with reference to Figure 1. First, the carbon substrate 14 is placed inside the reaction chamber 12 of the externally heated reduced-pressure CVD apparatus 10. The carbon substrate 14 is supported by a support means 15 having a support portion with a pointed tip.
[0018] Next, the reaction chamber 12 is heated. For example, the reaction chamber 12 is heated under conditions of 10 to 1000 Pa of atmospheric pressure and 800 to 2200°C of temperature.
[0019] Next, a tantalum carbide coating film is formed on the surface of the carbon substrate 14. As raw material gases, a gas containing carbon atoms such as methane (CH4) and a tantalum halogen gas such as hydrogen (H2) and tantalum pentachloride (TaCl5) are supplied from the raw material supply unit 16 to the reaction chamber 12. The tantalum halogen gas can be generated, for example, by heating and vaporizing tantalum halogen or by reacting tantalum metal with a halogen gas. Subsequently, the raw material gas supplied from the raw material supply unit 16 is subjected to a thermal CVD reaction at a high temperature of 800 to 2200°C and under a reduced pressure of 1 to 1000 Pa to form a tantalum carbide coating film on the carbon substrate 14.
[0020] Next, the supply of the raw material gas is stopped, and the carbon substrate 14 with the tantalum carbide coating film is left to stand at a high temperature of 800-2200°C and a reduced pressure of 1-1000 Pa to perform annealing. At this time, the pressure is adjusted by supplying an inert gas such as argon (Ar). This annealing process results in a number of particles of 10-10000 / mm² on at least a portion of the surface of the tantalum carbide coating material. 2 Pinholes can be made to exist at a density of . The temperature, pressure, and time of the annealing treatment can be appropriately changed depending on the desired pinhole density. The temperature of the annealing treatment is preferably 1000 to 2200°C, more preferably 1500 to 2200°C, and even more preferably 1800 to 2200°C. The pressure of the annealing treatment is preferably 5 to 500 Pa, more preferably 10 to 300 Pa, and even more preferably 50 to 200 Pa. The time of the annealing treatment is, for example, 1 to 300 hours, more preferably 2 to 250 hours, even more preferably 3 to 200 hours, even more preferably 3 to 150 hours, and even more preferably 3 to 100 hours.
[0021] The following explanation does not limit the present invention, but it is believed that annealing treatment can create pinholes on at least a portion of the surface of the tantalum carbide coated material for the following reasons. In general ceramic products, residual stress is reduced by heat treatment (annealing, after baking) after the ceramic product is manufactured. At the same time, it is known that annealing also fuses the crystal grains of the ceramic product, reducing the crystal interface areas that are vulnerable to thermal stress. Furthermore, when forming a metal carbide coating film using metal chlorides as raw materials by thermal CVD, as in the method for producing a tantalum carbide coating material according to one embodiment of the present invention, it is conceivable that the coating film may contain trace amounts of low-boiling-point raw material residue. These low-boiling-point raw material residues are thought to gradually accumulate at the grain boundaries under the high-temperature environment of the annealing process, and, combined with the fusion of the grain boundaries, reach a certain amount and volatilize. Ultimately, the areas where the volatilized raw material residues were present are observed as pinholes. It should be noted that, for general ceramic products, an annealing treatment may be performed after the ceramic product is produced, but the annealing treatment is not performed after forming a coating film on the surface of the ceramic product.
[0022] Pinholes are present at a density of 10 to 10000 per mm on at least a part of the surface of the tantalum carbide coated material 2 . If the density of the pinholes is less than 10 per mm 2 , the effect of increasing the number of repeated uses of the tantalum carbide coated material by the annealing treatment may not be exhibited. If the density of the pinholes exceeds 10000 per mm 2 , the processing time of the annealing treatment becomes long, which may increase the manufacturing cost of the tantalum carbide coated material or prolong the manufacturing time. The number of repeated uses of the tantalum carbide coated material may decrease. From such a viewpoint, the pinhole density of the tantalum carbide coated material is preferably 100 to 10000 per mm 2 , more preferably 500 to 10000 per mm 2 , still more preferably 1000 to 10000 per mm 2 , even more preferably 2000 to 10000 per mm 2 , even more preferably 3000 to 10000 per mm 2 , even more preferably 4000 to 10000 per mm 2 , even more preferably 5000 to 10000 per mm 2 , even more preferably 6000 to 10000 per mm 2 . The pinhole density of the tantalum carbide coated material can be measured by the method described in the Examples below.
[0023] The percentage of the area where pinholes exist at the above pinhole density on the entire surface of the tantalum carbide coated material is not particularly limited, but from the viewpoint of increasing the number of times the tantalum carbide coated material can be used repeatedly, it is preferably 50 to 100%, more preferably 60 to 100%, even more preferably 70 to 100%, even more preferably 80 to 100%, even more preferably 90 to 100%, even more preferably 95 to 100%, and especially preferably 100%.
[0024] The average value of the minor diameter of pinholes present in at least a portion of the surface of the tantalum carbide coated material is preferably 0.1 to 4.0 μm. An average value of 0.1 to 4.0 μm for the minor diameter of pinholes further increases the number of times the tantalum carbide coated material can be reused. From this viewpoint, the average value of the minor diameter of pinholes present in at least a portion of the surface of the tantalum carbide coated material is more preferably 1.0 to 3.0 μm, and even more preferably 1.5 to 2.5 μm. The average value of the minor diameter of pinholes can be measured by the method described in the examples below.
[0025] The thickness of the tantalum carbide coating film is preferably 3 to 100 μm. A thickness of 3 μm or more further improves the corrosion resistance of the tantalum carbide-coated carbon material. A thickness of 100 μm or less shortens the film formation time and improves the production efficiency of the tantalum carbide-coated carbon material.
[0026] The thermal expansion coefficient of the carbon substrate is preferably 4.0 to 8.0 × 10 -6 The temperature is / ℃. The thermal expansion coefficient of the carbon substrate is 4.0~8.0 × 10 -6 At a temperature of / °C, the occurrence of microcracks in the tantalum carbide coating can be further suppressed. Furthermore, the number of times the tantalum carbide coating material can be repeatedly used can be further increased. From this viewpoint, the thermal expansion coefficient of the carbon substrate is more preferably 4.0 to 7.5 × 10⁻⁶. -6 The temperature is / ℃, and more preferably 5.0 to 7.5 × 10 -6The temperature is / ℃, more preferably 6.0~7.5 × 10 -6 The temperature is / °C. The thermal expansion coefficient of the carbon substrate can be measured in accordance with JIS R 1618.
[0027] The tantalum carbide coating material of the above embodiment is an example of the carbide coating material of the present invention, and the carbide coating material of the present invention is not limited to tantalum carbide coating material. Furthermore, the carbide of the carbide coating material of the present invention is not limited to tantalum carbide. Examples of carbides of the carbide coating material of the present invention include tantalum carbide, niobium carbide, zirconia carbide, hafnium carbide, and tungsten carbide. These carbides can be used individually or in combination of two or more. Among these carbides, tantalum carbide is preferred because it has the highest melting point and excellent chemical stability, strength, and corrosion resistance.
[0028] The products used in the tantalum carbide coating material of the above embodiment were a crucible, a guide member, and a susceptor, but the products used in the metal carbide coating material of the present invention are not limited to a crucible, a guide member, and a susceptor.
[0029] [Regarding the manufacturing method of metal carbide coated materials] The present invention relates to a method for producing a metal carbide coated material, which includes a step of forming a metal carbide coating film on the surface of a carbon substrate by a CVD reaction using a metal chloride gas and a hydrocarbon gas. Preferably, the metal carbide coating film is formed in a temperature environment of 800 to 2200°C. Furthermore, the present invention relates to a method for producing a metal carbide coated material, which further includes a step of annealing the carbon substrate on which the metal carbide coating film has been formed at a high temperature of 800 to 2200°C and under a high-temperature, reduced-pressure environment of 1 to 1000 Pa. Note that each step has already been explained in the section on "Metal Carbide Coated Material," so the explanation of each step will be omitted here. [Examples]
[0030] The present invention will be described more specifically below with reference to examples, but the present invention is not limited to these examples.
[0031] The measurement and evaluation methods in this embodiment are as follows. <Pinhole observation on the surface of the tantalum carbide layer> Pinhole observation was performed on a tantalum carbide coating film deposited on the surface of a carbon substrate. A carbon substrate coated with tantalum carbide was cut to an appropriate size, and its surface was observed using a scanning electron microscope (SEM). At a magnification of 1000x and with appropriate electron beam settings, areas that appeared black and lacked material, and which were not continuous like microcracks, were defined as pinholes. Due to the SEM magnification being set to 1000x, a field of view of approximately 50 μm × 100 μm was obtained in one image. From this, a random 50 μm × 100 μm field of view was obtained, and the number of pinholes within it was measured. The same procedure was performed on 20 randomly selected fields of view for each sample, and the number of pinholes was tallied. Through this procedure, the number of pinholes was measured for a total of 100 μm × 1000 μm randomly selected fields of view. The pinhole density was then calculated using the following formula. Pinhole density (number of holes / mm²) 2 ) = (Number of pinholes in a randomly selected field of view totaling 100 μm × 1000 μm) × 10 Note that the calculation of pinhole density is based on 1 mm 2 You could observe the field of view for 1 mm, but from the standpoint of work efficiency, as mentioned above, 1 mm 2 Observing about one-tenth of the field of view was sufficient. Furthermore, the minor axis of the observed pinholes was measured, and the average, minimum, maximum, and standard deviation of the minor axis of the pinholes were calculated.
[0032] <Investigation of the number of times the product has been used repeatedly> A thermal cycling test was conducted to investigate the durability of a tantalum carbide coating film deposited on the surface of a carbon substrate. One cycle consisted of heating a sample for the durability test to 2200°C and holding it for 2 hours. After each cycle, the sample was checked for any defects or peeling of the tantalum carbide coating. If no defects or peeling were found, the cycle was repeated by heating the sample to 2200°C and holding it for 2 hours. If defects or peeling were found in the tantalum carbide coating, the cycle test was terminated, and the number of cycles performed was recorded.
[0033] <Thermal expansion coefficient of carbon substrates> The thermal expansion coefficient of the carbon substrate was measured in accordance with JIS R 1618.
[0034] <Arithmetic mean surface roughness Ra of carbon substrate> The arithmetic mean surface roughness Ra of the carbon substrate was measured according to JIS B 0633:2001 (ISO 4288:1996).
[0035] The tantalum carbide coated materials of Examples 1 to 17 and Comparative Example 1 were prepared as follows. The methods for preparing the tantalum carbide coated materials of Examples 1 to 17 and Comparative Example 1 will be explained with reference to Figures 1 and 2.
[0036] (Example 1) First, isotropic graphite was processed into cylindrical shapes (crucible 21) and frustoconical shapes (guide member 22), and these were used as carbon substrates 14. The arithmetic mean surface roughness Ra of these carbon substrates 14 was 6.0 μm, and the coefficient of thermal expansion (CTE) of these carbon substrates 14 was 7.2 × 10⁻⁶. -6 The temperature was / °C. The thermal expansion coefficient of the carbon substrate was measured using a thermomechanical analyzer (TMA7300) from Hitachi High-Tech Science Corporation in a temperature range from 200°C to 1200°C. Next, the carbon substrate 14 was placed in the reaction chamber 12 of the reduced-pressure CVD apparatus 10. The carbon substrate 14 was supported by a support means 15 having three support parts with pointed tips. At this time, the tips of the support parts were in contact with the outer surface of the cylindrical carbon substrate 14. Next, 0.25 SLM of methane (CH4) gas, 1.0 SLM of argon (Ar) gas and 0.125 SLM of hydrogen (H2) gas were supplied from the raw material supply unit 16, along with 0.25 SLM of tantalum pentachloride (TaCl5) that had been heated to 220°C and vaporized. The mixture was then reacted at a pressure of 100 Pa and a temperature of 1250°C in the reaction chamber 12 to form a tantalum carbide coating film over the entire surface of the carbon substrate 14. Subsequently, the reaction temperature was raised to 2200°C, and the temperature and pressure were maintained at 2200°C and 100 Pa for 5 hours to perform annealing, thereby producing the tantalum carbide coated material of Example 1. Two tantalum carbide coated materials were prepared: one for durability testing and another for pinhole measurement. The number of pinholes was measured for the carbon substrate 14 on which a tantalum carbide film was deposited, as described above. The pinhole density calculated at this time was 10 pins / mm 2 This was the calculated result. Durability evaluation was performed on a sample of carbon substrate 14 on which a tantalum carbide film was deposited, and it was able to withstand 48 thermal cycle tests.
[0037] (Example 2) The tantalum carbide coated material for Example 2 was prepared in the same manner as in Example 1, except that an annealing treatment was performed for 10 hours. The pinhole density was 280 pins / mm². 2 This was the calculated result. Furthermore, it was able to withstand 51 thermal cycle tests.
[0038] (Example 3) The tantalum carbide coated material for Example 3 was prepared in the same manner as in Example 1, except that an annealing treatment was performed for 20 hours. The pinhole density was 1890 pins / mm². 2 This was the calculated result. Furthermore, it was able to withstand 55 thermal cycle tests.
[0039] (Example 4) The tantalum carbide coated material of Example 4 was prepared in the same manner as in Example 1, except that an annealing treatment was performed for 40 hours. The pinhole density was 2650 pins / mm². 2This was the calculated result. Furthermore, it was able to withstand 60 thermal cycle tests.
[0040] (Example 5) The tantalum carbide coated material of Example 5 was prepared in the same manner as in Example 1, except that an annealing treatment was performed for 60 hours. The pinhole density was 4030 pins / mm². 2 This was the calculated result. Furthermore, it was able to withstand 68 thermal cycle tests.
[0041] (Example 6) The tantalum carbide coated material of Example 6 was prepared in the same manner as in Example 1, except that an annealing treatment was performed for 80 hours. The pinhole density was 6680 pins / mm². 2 This was the calculated result. Furthermore, it was able to withstand 76 thermal cycle tests.
[0042] (Example 7) The tantalum carbide coated material of Example 7 was prepared in the same manner as in Example 1, except that an annealing treatment was performed for 100 hours. The pinhole density was 8280 pins / mm². 2 This was the calculated result. Furthermore, it was able to withstand 88 thermal cycle tests.
[0043] (Example 8) The tantalum carbide coated material of Example 8 was prepared in the same manner as in Example 1, except that an annealing treatment was performed for 200 hours. The pinhole density was 9570 pins / mm². 2 This was the calculated result. Furthermore, it was able to withstand 86 thermal cycle tests.
[0044] (Example 9) The coefficient of thermal expansion is 4.0 × 10⁻⁶ -6 The tantalum carbide coated material of Example 9 was prepared in the same manner as in Example 1, except that a carbon substrate with a temperature of / ℃ was used. The pinhole density was 20 / mm². 2 This was the calculated result. Furthermore, it was able to withstand 18 thermal cycle tests.
[0045] (Example 10) The tantalum carbide coated material for Example 10 was prepared in the same manner as in Example 9, except that an annealing treatment was performed for 60 hours. The pinhole density was 5680 pins / mm². 2 This was the calculated result. Furthermore, it was able to withstand 26 thermal cycle tests.
[0046] (Example 11) The tantalum carbide coated material for Example 10 was prepared in the same manner as in Example 9, except that an annealing treatment was performed for 200 hours. The pinhole density was 9620 pins / mm². 2 This was the calculated result. Furthermore, it was able to withstand 29 thermal cycle tests.
[0047] (Example 12) The coefficient of thermal expansion is 5.3 × 10⁻⁶. -6 The tantalum carbide coated material of Example 12 was prepared in the same manner as in Example 1, except that a carbon substrate with a temperature of / ℃ was used. The pinhole density was 10 / mm². 2 This was the calculated result. Furthermore, it was able to withstand 34 thermal cycle tests.
[0048] (Example 13) The tantalum carbide coated material of Example 13 was prepared in the same manner as in Example 12, except that an annealing treatment was performed for 60 hours. The pinhole density was 3980 pins / mm². 2 This was the calculated result. Furthermore, it was able to withstand 38 thermal cycle tests.
[0049] (Example 14) The tantalum carbide coated material for Example 14 was prepared in the same manner as in Example 12, except that an annealing treatment was performed for 200 hours. The pinhole density was 9920 pins / mm². 2 This was the calculated result. Furthermore, it was able to withstand 44 thermal cycle tests.
[0050] (Example 15) The coefficient of thermal expansion is 6.5 × 10⁻⁶. -6 The tantalum carbide coated material of Example 15 was prepared in the same manner as in Example 1, except that a carbon substrate with a temperature of / ℃ was used. The pinhole density was 20 / mm². 2This was the calculated result. Furthermore, it was able to withstand 44 thermal cycle tests.
[0051] (Example 16) The tantalum carbide coated material of Example 16 was prepared in the same manner as in Example 15, except that an annealing treatment was performed for 60 hours. The pinhole density was 4630 pins / mm². 2 This was the calculated result. Furthermore, it was able to withstand 48 thermal cycle tests.
[0052] (Example 17) The tantalum carbide coated material of Example 17 was prepared in the same manner as in Example 15, except that an annealing treatment was performed for 200 hours. The pinhole density was 10210 pins / mm². 2 This was the calculated result. Furthermore, it was able to withstand 59 thermal cycle tests.
[0053] (Comparative Example 1) A tantalum carbide coated material for Comparative Example 1 was prepared in the same manner as in Example 1, except that annealing treatment was not performed. The pinhole density was 0 pins / mm². 2 This was the calculated result. Furthermore, it was able to withstand 30 thermal cycle tests.
[0054] Table 1 shows the evaluation results for Examples 1-17 and Comparative Example 1. [Table 1]
[0055] In Examples 1-8 and Comparative Example 1, the values were 7.2 × 10⁻⁶. -6 The results when using a carbon substrate with a thermal expansion coefficient (CTE) of / °C can be seen. Here, it can be confirmed that as the annealing time increases, the pinhole density increases, and the number of repeated uses increases (see Figure 3).
[0056] In Examples 9-11, 4.0 × 10 -6The results when using a carbon substrate with a thermal expansion coefficient (CTE) of / °C can be seen. Here, it can be confirmed that as the annealing time increases, the pinhole density increases, and the number of repeated uses increases (see Figure 3).
[0057] In Examples 12-14, 5.3 × 10 -6 The results when using a carbon substrate with a thermal expansion coefficient (CTE) of / °C can be seen. Here, it can be confirmed that as the annealing time increases, the pinhole density increases, and the number of repeated uses increases (see Figure 3).
[0058] In Examples 15-17, 6.5 × 10 -6 The results when using a carbon substrate with a thermal expansion coefficient (CTE) of / °C can be seen. Here, it can be confirmed that as the annealing time increases, the pinhole density increases, and the number of repeated uses increases (see Figure 3).
[0059] Regarding Examples 1-17, we examined the pinhole shape profiles. Looking at the average value of the pinhole's minor diameter, no significant differences were observed among Examples 1-17. Except for Examples 1, 9, 12, and 15, which had a small number of pinhole calculations, no significant differences were observed in the minimum, maximum, or standard deviation of the pinhole's minor diameter.
[0060] From these results, the degree of annealing can be estimated by calculating the pinhole density on the surface of the tantalum carbide coating, and a correspondingly durable tantalum carbide coated carbon material can be obtained. [Explanation of Symbols]
[0061] 10. External Heating Type Reduced Pressure CVD Apparatus 11 Top Chamber 12 Reaction Chambers 13 Heater 14 Carbon substrate 15 Support means 16 Raw material supply department 17 Exhaust section 20 SiC single crystal growth apparatus 21 Crucible 22 Guide member 23 Upper lid 24 SiC seed crystal 25 SiC raw material
Claims
1. A metal carbide coating material comprising a carbon substrate mainly composed of carbon, and a metal carbide coating film mainly composed of metal carbide that covers at least a portion of the carbon substrate, At least a portion of the surface of the aforementioned metal carbide coating material has 10 to 10,000 particles / mm². 2 A metal carbide coated material in which pinholes exist at a density of [value].
2. The metal carbide coating material according to claim 1, wherein the average value of the minor diameter of the pinholes is 0.1 to 4.0 μm.
3. The metal carbide coating material according to claim 1, wherein the metal carbide coating film is mainly composed of at least one metal carbide selected from the group consisting of tantalum carbide, niobium carbide, zirconium carbide, hafnium carbide, and tungsten carbide.
4. The thermal expansion coefficient of the carbon substrate is 4.0 to 8.0 × 10 -6 The metal carbide coating material according to claim 1, wherein the temperature is / °C.
5. The metal carbide coated material according to claim 1, wherein the thickness of the metal carbide coating film is 3 to 100 μm.
6. A method for producing a metal carbide coated material according to any one of claims 1 to 5, comprising the step of forming the metal carbide coating film on the surface of the carbon substrate by a CVD reaction using a metal chloride gas and a hydrocarbon gas.
7. The method for producing a metal carbide coated material according to claim 6, wherein the metal carbide coating film is formed in a temperature environment of 800 to 2200°C.
8. A method for producing a metal carbide coated material according to claim 6, further comprising the step of performing an annealing treatment of the carbon substrate having the metal carbide coating film formed on its surface at a high temperature and reduced pressure of 800 to 2200°C and 1 to 1000 Pa.
Citation Information
Patent Citations
Tantalum carbide coating carbon material and method of manufacturing the same, and member for semiconductor single-crystal manufacturing apparatus
JP2019099453A
METHOD OF MANUFACTURING TaC COATING LAYER USING CVD AND PROPERTY OF TaC MANUFACTURED USING THE SAME
JP2019108611A